2021
DOI: 10.1016/j.cpr.2021.102063
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of adapted psychological interventions for people from ethnic minority groups: A systematic review and conceptual typology

Abstract: This review assessed the efficacy of adapted psychological interventions for Black and minority ethnic (BME) groups. A conceptual typology was developed based on adaptations reported in the literature, drawing on the common factors model, competence frameworks and distinctions between types of cultural adaptations. These distinctions were used to explore the efficacy of different adaptations in improving symptoms of a range of mental health problems for minority groups. Bibliographic searches of MEDLINE, Embas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 114 publications
2
73
0
1
Order By: Relevance
“…Even though not widely researched, the acceptability of the intervention significantly affects take-up and dropout rates [ 17 ]. A recent review shows the relevance of adapted interventions for racial and ethnic minorities [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though not widely researched, the acceptability of the intervention significantly affects take-up and dropout rates [ 17 ]. A recent review shows the relevance of adapted interventions for racial and ethnic minorities [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the authors’ knowledge, this is the first large-scale outcomes evaluation of a culturally responsive video BCT program across racial and ethnic groups. Prior meta-analyses have reported greater effects for culturally adapted psychological interventions compared to unadapted or no psychological intervention among communities of color [ 44 , 45 ], including culturally-adapted internet-based psychological interventions [ 17 ]. However, unlike the BCT program evaluated in the current study, most of the interventions included in those analyses were adapted for specific racial and ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…A 2016 meta-analysis found that these cultural adaptations were almost five times more likely to produce remission from psychopathology than control conditions (e.g., no intervention or other interventions; Hall et al, 2016). A recent meta-analysis of randomized controlled trials found that Black and ethnically diverse groups experienced greater symptom improvements from culturally adapted interventions as compared to nonadapted active interventions (Arundell et al, 2021). A growing number of systematic reviews and meta-analyses similarly find moderate to large effects for culturally adapted EBTs (see Rathod et al, 2018, for a review of meta-analyses).…”
Section: Dbtmentioning
confidence: 99%
“…Still, this definition is vague about what constitutes a “modification”—this could range from those that are superficial (e.g., using quotes from culturally relevant figures) to deep (e.g., removing entire DBT skills to be more congruent with a client’s cultural context). Recently, a typology of cultural adaptations was proposed based on meta-analyses of therapies adapted for people of color (Arundell et al, 2021). In this framework, cultural adaptations are classified as either therapist related (e.g., ethnic matching, therapist training, provider language), content related (e.g., use of religious texts, materials translation, culturally sensitive terms), or organization specific (e.g., location of treatment, length of intervention, method of access).…”
Section: Dbtmentioning
confidence: 99%